A CORRELATION BETWEEN TRAINING, PROMOTION, IMAGING AND PUBLIC INTEREST WITH INCREASE OF SALE IN PRODUCT OF â€œBATIK TULISâ€ IN LAWEYAN, SURAKARTA. - Sujanto, Muhammad (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
The purpose of this research is to detect: (1) a correlation between batik training with increase of sale in product of batik, (2) a correlation between batik promotion with increase of sale in product of batik, (3) a correlation between batik imaging with increase of sale in product of batik, (4) a correlation between public interest with increase of sale in product of batik, (5) a correlation between training, promotion, imaging and public interest with increase of sale in a product of ?batik tulis? in Laweyan, SurakartaThe research uses quantitative method. The research population is a whole entrepreneur and devotee of batik in Laweyan, Surakarta. A sample was took through Purposive Sampling technique. The data collection techniques use questionnaire and documentation. A data analysis technique was used with correlation test and double regression technique.Based on the results of research can be concluded that: (1) there is positive correlation and significant between batik training with increase of sale in a product of batik in Laweyan, Surakarta, (2) there is positive correlation and significant between batik promotion with increase of sale in a product of batik in Laweyan, Surakarta, (3) there is positive correlation and significant between imaging batik with increase of sale in a product of batik in Laweyan, Surakarta, (4) ) there is positive correlation and significant between public interest with increase of sale in a product of batik in Laweyan, Surakarta, (5) there are positive correlation and significant collectively between training, promotion, imaging and public interest with increase of sale in a product of batik in Laweyan, SurakartaKeywords : ?Batik Tulis?, Product, Promotion and Imaging